The Chemo-Gut Study: A Cross-Sectional Survey Exploring Physical, Mental, and Gastrointestinal Health Outcomes in Cancer Survivors - Julie M. Deleemans; Kirsti Toivonen; Raylene A. Reimer; Linda E. Carlson (SAGE Publishing, 2022)
Background Cancer treatments, such as chemotherapy, may adversely affect gastrointestinal (GI), physical and mental health in survivors of cancer. Objective This study investigated associations between GI, mental and physical health outcomes, and cancer treatment-related variables, such as chemotherapy, in adult cancer survivors. Methods A one-time cross-sectional survey with patient-reported outcomes was used. Cancer survivors (N = 317) aged ≥18 years, living in Canada, who completed cancer treatments were included. Descriptive statistics, correlation, and linear regression analyses are reported. Results Mean age at diagnosis was 40.90 ± 15.40 years. Most survivors received chemotherapy (86.1%). Persistent GI symptoms include constipation (53.6%), diarrhea (50.5%), and bloating/pain (54.9%). Mean GI symptom duration was 30.53 ± 33.42 months. Severity of GI symptom interference was moderate to extreme for 51.9% of survivors. Compared to normative values of 50 in healthy people, survivors scored poorer for mental health (M = 42.72 ± 8.16) and physical health (M = 45.55 ± 7.93), and reported more belly pain (M = 56.10 ± 8.58), constipation (M = 54.38 ± 6.81), diarrhea (M = 55.69 ± 6.77), and gas/bloating (M = 56.08 ± 8.12). Greater GI symptom severity was associated with poorer mental and physical health ( P < .01). Chemotherapy was associated with increased belly pain ( B = 4.83, SE = 1.65, P < .01) and gas/bloating ( B = 3.06, SE = 1.45, P = .04). Conclusion We provide novel evidence that many cancer survivors experience chronic, moderate to severe GI symptoms lasting for years after cancer treatment, which are associated with worse mental and physical health. Chemotherapy is associated with specific GI symptoms. Integrative therapies are needed to address GI symptoms in cancer survivors.